The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1002/1097-4679(197607)32:3<644::aid-jclp2270320333>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Internal-external control, defensiveness, and anxiety in hypertensive patients

Abstract: PROBLEM Previous research has suggested that beliefs in internal-external control (19) may be related to the degree of an individual's emotional adjustment and the kinds of defenses used to cope with stressful events. Externally oriented individuals have been found to report more anxiety and endorse more deviant or pathological items on a variety of stlf-report personality measure^ (^^ 12, 17) than internals, who tend to report less anxiety but rely more heavily on the defenses of denial and repression@* 12).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…For example, aware hypertensives have not been found to differ from medical and surgical patients (4), ulcer patients and general illness patients (10), chronically ill outpatients (74), normotensive patients attending a general medical clinic (11,17,21), cardiovascular disease patients (12), or patients with secondary hypertension (13,15). The conclusion based upon these studies, taken together, may be that the influence of disease knowledge on personality parameters is a general phenomenon which is associated with many different medical conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, aware hypertensives have not been found to differ from medical and surgical patients (4), ulcer patients and general illness patients (10), chronically ill outpatients (74), normotensive patients attending a general medical clinic (11,17,21), cardiovascular disease patients (12), or patients with secondary hypertension (13,15). The conclusion based upon these studies, taken together, may be that the influence of disease knowledge on personality parameters is a general phenomenon which is associated with many different medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of the earlier empirical literature concluded that neuroticism (2), hostility, and difficulties in coping with anger were associated with hypertension (3). However, much of this work suffers from major methodological flaws, including inadequate methods to diagnose hypertension and the use of unvalidated measures of personality, and is confounded by the recruitment of subjects from hypertension treatment centers and the use of antihypertensive medications (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Moreover, little attention has been given to the importance of differential exposure to medical attention and hypertension labeling as determinants of personality.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of defensiveness have been associated with cardiovascular‐related morbidity and mortality (Dimsdale & Hackett, 1982; Helmers et al, 1995; Jorgensen et al, 2001; Rutledge, Linden, & Davies, 2000), hypertension (Kidson, 1973; Linden & Feuerstein, 1983; Mann & James, 1998; Rutledge & Linden, 2000; Santonasto, Canton, Ambrosio, & Zamboni, 1984; Wennerholm & Zarle, 1976), and elevations in blood pressure (BP; Jamner, Shapiro, Goldstein, & Hug, 1991; Jorgensen, Johnson, Kolodziej, & Schreer, 1996; King, Taylor, Albright, & Haskell, 1990; Nyklicek, Vingerhoets, Van Heck, & Van Limpt, 1998; Rutledge & Linden, 2003), lipids (Niaura, Herbert, McMahon, & Sommerville, 1992), and glucose levels (Jamner, Schwartz, & Leigh, 1988). Older women who are elevated on defensiveness exhibit an increased metabolic burden, placing them at higher risk for disease development (Lévesque et al, 2009).…”
mentioning
confidence: 99%
“…Existing evidence suggests that this style of ''defensive'' or ''repressive'' coping is associated with hypertension. [35][36][37] Studies in which defensiveness was assessed by questionnaires such as the Marlowe-Crowne Scale of Social Desirability have reported a consistent relationship between defensiveness and hypertension. 9,18,35,38 In addition, in a study that was unique in including patients with severe hypertension, the condition was associated with defensiveness and not with perceived anger or anxiety.…”
Section: Defensiveness and Repressive Copingmentioning
confidence: 99%
“…Existing evidence suggests that this style of “defensive” or “repressive” coping is associated with hypertension 35–37 . Studies in which defensiveness was assessed by questionnaires such as the Marlowe‐Crowne Scale of Social Desirability have reported a consistent relationship between defensiveness and hypertension 9,18,35,38 .…”
Section: Role Of Repressed Vs Consciously Experienced Emotionmentioning
confidence: 99%